Notes to Philosophy 167: Class 1 -- Overview of the Course;Ptolemaic Astronomy -- Part 4. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Problem of the Planets -- Classical Greek Solutions.; Generally corresponds to the video segment: Class 1, Part 4.